Genetic determinants of adverse outcome (restenosis, malapposition and thrombosis) after stent implantation. (April 2010) - Bergheanu, Sandrin C; Pons, Douwe; Karalis, Ioannis; ÖÖzsoy, Orççun; Verschuren, Jeffrey JW; Ewing, Mark M; Quax, Paul HA; Jukema, J Wouter
Despite its unequivocal superiority compared with balloon angioplasty, coronary stenting did not abolish the restenosis problem and even brought along a completely new type of pathology. Bare-metal stents still associate with an approximate 20––30% in-stent restenosis rate and the need for repeat revascularization. Drug-eluting stents (which unfortunately did not completely prevent restenosis either) sometimes determine late-acquired stent malapposition in a significant number of patients. This is occasionally followed by a very serious event –– stent thrombosis. Patient comorbidities, stent design, procedural characteristics and antiplatelet therapy influence the risk of poststenting complications. Research in the recent years has also revealed that individual genetic profile plays an important role in adverse outcome after stent implantation. This article reviews the evidence of genetic variations associated with stent restenosis, late-acquired stent malapposition and stent thrombosis.